2020
DOI: 10.1111/risa.13574
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming Risk Perceptions in India

Abstract: Few studies have focused on global warming risk perceptions among people in poor and developing countries, who are disproportionately impacted by climate change. This analysis conducts a comprehensive assessment of global warming risk perceptions in India using a national sample survey. Consistent with cultural theory, egalitarianism was positively associated with global warming risk perceptions. In addition, perceived vulnerability and resilience to extreme weather events were also two of the strongest factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…That most of the studies we reviewed focus on the Global North is problematic in generating theory on affect and climate risk perception and communication. For example, Thaker et al (2020) found that existing frameworks developed in the Global North could not adequately explain affective responses in India. This is particularly important, as people in the Global South are disproportionately experiencing the impacts of climate change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That most of the studies we reviewed focus on the Global North is problematic in generating theory on affect and climate risk perception and communication. For example, Thaker et al (2020) found that existing frameworks developed in the Global North could not adequately explain affective responses in India. This is particularly important, as people in the Global South are disproportionately experiencing the impacts of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of affective dimensions in risk communication relied on affective imagery to investigate positive and negative emotions triggered by images, sounds, ideas, and stories which evoke judgment of a perceived risk (Lorenzoni et al, 2006;Smith and Leiserowitz, 2012;Thaker et al, 2020). It is notable that many studies did not explicitly follow a specific theory of affect despite the growing number, diversity and contrasts between different theories of affect (Furtak, 2018).…”
Section: Meanings and Understandings Of Affectmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in the literature, increasing attention has been given to perceived vulnerability and awareness of climate change [33,41,42], as it has been demonstrated that there is a strong link between perceptions and adaptation [11,[14][15][16][43][44][45][46]. Likewise, the relationship between perceived vulnerability and bio-physical data has also been studied and it was concluded that there is a positive trend between them [42,47]. However, there is also evidence of an underestimation of bio-physical vulnerability and how it is affected by social, psychological, and demographic variables.…”
Section: Vulnerability To Climate Change and Adaptationmentioning
confidence: 99%